Polymorphism of mitochondrial tRNA genes associated with the number of pigs born alive. Issue 1 (December 2018) - Wang, Dan; Ning, Chao; Xiang, Hai; Zheng, Xianrui; Kong, Minghua; Yin, Tao; Liu, Jianfeng; Zhao, Xingbo
Abstract Background Mutations in mitochondrial tRNA genes have been widely reported association with human reproductions. It is also important to explore the effect on the number of piglets born alive (NBA). Here, 1017 sows were used to investigate the association between polymorphisms in mitochondrial tRNA genes and NBA. Results In total, 16 mutations were found in mitochondrial tRNA genes, of which 13 mutations were significantly associated with NBA (P < 0.05). The reproductions of mutant carriers were significantly greater than that of wild carriers by 0.989 piglets born alive/sow farrowing. To test whether the mutations altered the structure of mitochondrial tRNAs, the secondary and tertiary structures were predicted. In result, C2255T changed the secondary structure of tRNA-Val by elongating the T stem and shrinking the T loop, and C2255T and G2259A in the tRNA-Val gene, C6217T and T6219C in the tRNA-Ala gene, and T15283C in the tRNA-Glu gene altered the tertiary structure of their tRNAs, respectively by changing the folding form of the T arm, and C16487T in the tRNA-Thr gene changed the tertiary structure of mitochondrial tRNA-Thr by influencing the folding form of the acceptor arm. Conclusions Results highlight the effect of mitochondrial tRNA genes on the number of piglets born alive, and suggest that polymorphic sites of the tRNA genes be genetic markers for selection of pig reproduction.